Permainan Ular Tangga dengan Benda Asli sebagai Media Penyuluhan Pengendalian Jentik pada Anak Sekolah Dasar - Chairunnisa Roosmandasari; Sardjito Eko Windarso; Heru Subaris Kasjono (Sanitasi: Jurnal Kesehatan Lingkungan, 2020)
Dengue haemorrhagic fever every year become a major health problem because many areas have free-larvae-index below the standard 95%. Counseling by teaching and in persuasive context need to be implemented to elementary school children, include for DHF problems. The purpose of this study was to reveal the knowledge level difference among the children between counseling with talking method and counseling with snake and ladder game with real object as a media. This quasi experiment was conducted following non equivalent control group design, with 37 fifth grade students of Jatisawit Elementary School, in Balecatur, Gamping as the respondents, on May 2018. They were allocated into two groups, i.e. 19 students in the experimental group and 18 in the control group. Descriptively, characteristics of respondents regarding to age and gender are no different between the two groups. The data analysis shows that the intervention media game with real object significantly increased the knowledge level (p value of 0,02), meanwhile in the control group the increased was not significant (p value of 0,747). With independent t-test, the knowledge level increase difference between the two methods is also confirmed (p value of 0,02).